2000
DOI: 10.1080/03014460050044865
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and performance of world championship triathletes

Abstract: Performance is related to body morphology in many sports. With triathlon making its debut into the Olympic programme in 2000, it was deemed important to determine which physical characteristics of elite-level triathletes were significantly related to performance. Seventy-one elite and junior elite triathletes, from 11 nations, competing at the 1997 World Triathlon Championships were measured on a battery of 28 anthropometric dimensions. A factor analysis was conducted, which reduced the number of variables to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
3
15

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 10 publications
8
77
3
15
Order By: Relevance
“…The mean and standard deviation of normalized overall race time in Olympic distance triathlon for male triathletes (6827.57 ± 192.56 [s]; approximately 1:54 h) calculated in this study were comparable to those reported by Landers et al (2000). A closer look at the Top 10 ranked athletes in the WTS from 2009 until 2012 showed that the mean ± SD of overall race time were consistent with the values used, considering that German elite triathletes commonly have a Top 20 position in WTS races.…”
Section: Normalization Of Race Timesupporting
confidence: 78%
See 2 more Smart Citations
“…The mean and standard deviation of normalized overall race time in Olympic distance triathlon for male triathletes (6827.57 ± 192.56 [s]; approximately 1:54 h) calculated in this study were comparable to those reported by Landers et al (2000). A closer look at the Top 10 ranked athletes in the WTS from 2009 until 2012 showed that the mean ± SD of overall race time were consistent with the values used, considering that German elite triathletes commonly have a Top 20 position in WTS races.…”
Section: Normalization Of Race Timesupporting
confidence: 78%
“…This could possibly be a drawback of subjective assessments compared to the exploratory factor analysis as a purely statistical approach, which sorted out VO 2 max. Landers et al (2000) underlined the importance of identifying parameters predicting race performance. Besides potentially supporting the creation of new training programs, the information provided by performance prediction models could also be used in the field of talent diagnostics.…”
Section: Preselection Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different factors influencing performance in endurance exercise (17). Apart from physiological parameters, several anthropometric parameters show an association with endurance performance such as body mass (2,26), body mass index (BMI), body fat (1,21), length of the upper leg (29), length of limbs (19), body height (2), circumference of thigh (29), total skin-fold thickness (2) and skin-fold thickness of the lower limb (1,21).…”
Section: Introductionmentioning
confidence: 99%
“…Mundialmente, el atletismo es una de las disciplinas deportivas más destacadas, para la cual se han hecho diferentes mediciones antropométricas y morfológi-cas (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Al comparar los resultados de este estudio con los de corredores de mediofondo españoles de nivel nacional o internacional (10), se puede afirmar que el promedio de peso corporal, porcentaje graso y porcentaje muscular fueron superiores a los reportados en este estudio.…”
Section: Discussionunclassified